Phenomenon of the Use of Code-Switching of Balinese People Daily Communication in Buleleng Regency - Ni Putu Wirliana Windicha Putri (Linguistics Initiative, 2022)
This study aims to analyze the types and functions of code-switching used in the daily conversation of Balinese people. This research was conducted in Tinga-tinga village, located in the Buleleng Regency, Gerokgak District, Bali Province. The participants or subject of this research were the surrounding people in the Tinga-tinga village. The instruments used in this research were observation and interview. The data was analyzed using a descriptive qualitative design to describe the result of the study in the Buleleng Regency daily conversation. After collecting data by conducting observations and interviews, this research found that people in Buleleng Regency mostly do code-switching in their everyday conversations using the local language or Bahasa Bali and Indonesian language or Bahasa Indonesia. The type of code-switching often used among the community is intra-sentential switching. People often do code-switching from one language to another in one sentence when communicating and when they find it difficult to explain something using the local language. On the other hand, the function of code-switching that Buleleng people often use is the referential function. They use the function to explain or express something in simple language that listeners easily understand. In addition, the function often used is the expressive function of code-switching.